A new species of Bauhinia ser. Cansenia (Cercidoideae, Leguminosae) endemic to the Atlantic Forest in the state of Bahia, Brazil - Santos, Antonio C.b. Dos; Queiroz, Luciano P. De; Paula, Antonio P.o.; Carvalho, Reginaldo De (Phytotaxa, 2022)
The genus Bauhinia belongs to the subfamily Cercidoideae (Leguminosae) and includes ca. 230 species with pantropical distribution. Sixty-two species are recorded in Brazil, 20 of which occur in the northeastern Brazilian state of Bahia. The genus is classified in eight sections, with sect. Pauletia being the most diverse. This article describes Bauhinia arleneae, a new species from this section, restricted to the humid forests of the central-eastern region of the state of Bahia. The new species is morphologically similar to B. cinnamomea, with both species sharing entire and elliptical leaves with acuminate apex and flowers paired along the pseudoracemes. B. arleneae differs from B. cinnamomea by the slender and flexuous multi-stemmed shrub or treelet habit, with glabrous leaves with 3 to 5 primary veins and fruit with coriaceous-woody, reticulate valves. We provide a description, illustrations, and a distribution map for the new species.